The Derived Process of Derivational Morpheme Found in The Power of a Positive Wife Book - Ni Putu Sumariani; Ida Bagus Gde Nova Winarta; I Gusti Bagus Wahyu Nugraha Putra (International Journal of English Learning and Applied Linguistics (IJELAL), 2021)
The purpose of the research is to describe the derived process of derivational morpheme found in “The Power of a Positive Wife Book” This study focused on: The derived process of each derivational morpheme used in “The Power of a Positive Wife Book.”  Qualitative and supported by quantitative method was used in this research and the data source was “The Power of a Positive Wife” Book. The method used in collecting the data was descriptive qualitative method. The result of the analysis was presented by using formal and informal method. In affixes, have three types as follows: suffix, infix and prefix. There are nine types of derived process of derivational morpheme such as Noun derived from Adjective, Adjective derived from Noun, Noun derived from Noun, Verb derived from Verb, Noun derived from Verb, Adjective derived from Adjective, Verb derived from Noun, Adjective derived from Verb and Adverb derived from Adjective. The frequencies of each kind of derivational morpheme are different to each other. The most frequently occurring were derived adverb from adjective and the most rarely occurring was derived Adjective from Adjective. Derived verb from Adjective and derived adjective from verb were not found in this data source.  The total data of derivational morpheme found in The Power of a Positive Wife Book was 195 words.